Investasi Modal Manusia dan Implikasinya terhadap Efektivitas Promotional Pricing: Peran Mediasi Kapabilitas Pemasaran pada Industri Internet Service Provider - Gilang Bhirawa Noraga; Ujang Permana (Journal of Knowledge Management, 2026)
This research undertakes an examination of the extent to which Training and Development (T&D) initiatives impact the effectiveness of Promotional Pricing, mediated by the construct of Marketing Capability, among employees engaged with Internet Service Provider (ISP) firms situated in the Suciayumajakuning region of Indonesia, encompassing Subang, Cirebon, Indramayu, Majalengka, and Kuningan. Leveraging Human Capital Theory (Becker, 1993), Dynamic Capability Theory (Teece et al., 1997), and the Resource-Based View (Barney, 1991), this investigation explores the manner in which enhancements in employee competencies can serve as a catalyst for improved marketing performance and the adaptability of pricing strategies within a fiercely competitive digital marketplace. Employing a quantitative methodology alongside Structural Equation Modeling–Partial Least Squares (SEM-PLS), data were systematically gathered from a sample of 150 marketing and promotional personnel employed by ISPs. The findings indicate that T&D exerts a significant influence on Marketing Capability (β = 0.613, p < 0.001), which subsequently has a strong impact on Promotional Pricing (β = 0.582, p < 0.001). Additionally, a modest yet statistically significant direct effect of T&D on Promotional Pricing (β = 0.176, p < 0.05) was identified, while the indirect effect (β = 0.357) substantiates the mediating function of Marketing Capability. These results underscore the critical strategic significance of investing in human resources to enhance marketing agility and optimize pricing effectiveness within service-oriented industries.. Keywords: Training and Development; Marketing Capability; Promotional Pricing; SEM-PLS; ISP Industry.